Mixed Matrix Membranes (MMMs) Comprising Exfoliated 2D Covalent Organic Frameworks (COFs) for Efficient CO2 Separation - Kang, Zixi; Peng, Yongwu; Qian, Yuhong; Yuan, Daqiang; Addicoat, Matthew A; Heine, Thomas; Hu, Zhigang; Tee, Lincoln; Guo, Zhengang; Zhao, Dan (Chemistry of materials, 2016)
Two water-stable covalent organic frameworks (COFs) named NUS-2 and NUS-3 having two-dimensional (2D) layered structures with different pore sizes were synthesized. These COFs were exfoliated into nanosheets and even monolayers with high aspect ratio. They were subsequently blended with commercial polymers poly(ether imide) (Ultem) or polybenzimidazole (PBI) into mixed matrix membranes (MMMs) exhibiting highly homogeneous textures due to the excellent compatibility between COF fillers and polymer matrixes. Thanks to the selective gas sorption properties of the porous COF fillers, the prepared MMMs exhibited increased gas permeabilities with NUS-2@PBI demonstrating an excellent H2/CO2 permselectivity that exceeded the 2008 Robeson upper bound. Our approach of using exfoliated 2D COFs as porous fillers in MMMs paves a novel way toward the tailored synthesis of advanced composite membrane materials for clean energy and environmental sustainability.